Scapanoclypeus bicoloratus new species from Hardap, Namibia (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) - Sehnal, Richard (Zootaxa, 2017)
Scapanoclypeus Evans (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) was established with Trichinopus aberrans Frey designated as its type species and included five additional species: S. testaceus Evans, S. carinatus Evans, S. cornutus Evans, S. brunneus Evans, and S. aulacocoleatus Evans. Scapanoclypeus, Trichinopus Waterhouse, and Oedanomerus Waterhouse are distinguished from other African Tanyproctini by their small size (12 mm or less), reduced mouthparts, and antennae with 8–10 antennomeres (Evans 1987). Species of Scapanoclypeus and Oedanomerus have simple claws without cleft or teeth at base, a slightly conical labrum, and a third antennomere that is equal in length to the fourth; while Trichinopus has bifid claws, a distinctly conical labrum with rounded end, and the third antennomere approximately as long as the fourth (Lacroix 2007). The antennal club of Scapanoclypeus is at least three times longer than the combined length of antennomeres I–IV and the clypeal surface at nearly a right angle in relation to the plane of the frons, while Oedanomerus has an antennal club about as long as the combined length of antennomeres I–IV and coplanar clypeal and frontal surfaces (Evans 1987; Lacroix 2007; Sehnal 2013). Scapanoclypeus was subsequently mentioned in Lacroix (2007), who re-drew the figures and adopted the key from Evans (1987). Three additional species have since been described from southern Africa: S. triapicalis Sehnal, S. sinepunctatus Sehnal, and S. hardap Sehnal (see Sehnal 2013, 2014).